Money Beliefs dalam Pengelolaan Keuangan Siswa SMK Negeri 8 Palangka Raya - Dewi Rakhmawati; Sanjayanto Nugroho; Dhina Sri Widyaningsih (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of beliefs about money, the social and media environment on financial management behavior among students of SMK Negeri 8 Palangka Raya. This study uses a quantitative associative approach with an exploratory design. Data were collected from 100 respondents using a Likert-scale questionnaire and analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method. The results show that beliefs about money, the social and media environment both have a positive and significant influence on students' financial management behavior. Beliefs about money emerged as the most dominant factor influencing financial management, indicating that students with a positive perception of money—as a means to achieve goals rather than a status symbol—are better able to manage their personal finances effectively. Furthermore, the social and media environment were found to act as moderators, strengthening the relationship between beliefs about money and financial management behavior.